Pelatihan Pengembangan Media Pembelajaran Interaktif Berbasis Canva untuk Meningkatkan Kompetensi Digital Guru TK - Andi Nur Maharani Islami; Rika Kurnia R; Fadhilah Afifah; Ramlah Yusran; Andi Makkasau (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to enhance the digital competence of 20 kindergarten teachers in Bajeng District, Gowa Regency, in developing interactive learning media using the Canva application. The issues faced by the partners included low teacher digital literacy regarding the design of technology-based learning media and minimal utilization of online graphic design applications in early childhood education. The activity employed a participatory "learning-by-doing" approach, comprising needs assessment and orientation, training, hands-on media creation, classroom implementation, and ongoing mentoring. Teacher competence was measured using a pre-test and post-test instrument consisting of 10 multiple-choice questions covering four indicators: digital literacy and competence, principles of visual learning design, mastery of basic Canva features, and the application of interactive media in instruction. The results showed an increase in the average score from 42 in the pre-test to 96 in the post-test. The activity also produced an innovative product Canva-based "Interactive Digital Story Cards" designed to support storytelling and vocabulary acquisition within thematic early childhood learning; this product was implemented in classrooms and elicited a positive response from children regarding interest, participation, and comprehension. These findings indicate the effectiveness of practice-based training in enhancing teachers' digital competence while supporting the transformation of early childhood education toward innovative, creative, and contextual learning in the digital era.